2021
DOI: 10.1002/smll.202101093
|View full text |Cite
|
Sign up to set email alerts
|

Bean‐Pod‐Inspired 3D‐Printed Phase Change Microlattices for Solar‐Thermal Energy Harvesting and Storage

Abstract: Effective and reliable encapsulation of phase change materials (PCMs) is essential and critical to the high‐performance solar‐thermal energy harvesting and storage. However, challenges remain pertaining to manufacturing scalability, high efficiency in energy storage/release, and anti‐leakage of melted PCMs. Herein, inspired by natural legume, a facile and scalable extrusion‐based core‐sheath 3D printing strategy is demonstrated for directly constructing bean‐pod‐structured octadecane (OD)/graphene (BOG) phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Recent years have seen tremendous efforts in fabricating wearable phase-change fabrics, in which the frequently used PCMs include two distinct categories of solid–liquid and solid–solid in terms of the phase-change process. Via impregnating PCM under vacuum into a matrix with open and hierarchical pores, a variety of solid–liquid PCMs has been extensively explored for phase-change fabrics. However, the impregnation process is time-consuming and prone to cause inhomogeneous distribution of PCMs, especially high risks of liquid leakage during multiple endothermal and exothermal processes is a long-standing bottleneck for their broad-scale practical applications. , Alternatively, solid–solid phase-change fabrics as a promising candidate, constructed with various flexible polymers including the olefin block copolymer, poly­(vinyl chloride), poly­(methyl methacrylate), thermoplastic polyurethane (TPU), and polyethylene, are triggering a boom in wearable fields owing to their excellent maintenance of the solid state and no substantial leakage during phase transitions. Nevertheless, the as-fabricated phase-change fabrics still suffer from a complicated manufacturing procedure and poor shape stability during the phase-change process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen tremendous efforts in fabricating wearable phase-change fabrics, in which the frequently used PCMs include two distinct categories of solid–liquid and solid–solid in terms of the phase-change process. Via impregnating PCM under vacuum into a matrix with open and hierarchical pores, a variety of solid–liquid PCMs has been extensively explored for phase-change fabrics. However, the impregnation process is time-consuming and prone to cause inhomogeneous distribution of PCMs, especially high risks of liquid leakage during multiple endothermal and exothermal processes is a long-standing bottleneck for their broad-scale practical applications. , Alternatively, solid–solid phase-change fabrics as a promising candidate, constructed with various flexible polymers including the olefin block copolymer, poly­(vinyl chloride), poly­(methyl methacrylate), thermoplastic polyurethane (TPU), and polyethylene, are triggering a boom in wearable fields owing to their excellent maintenance of the solid state and no substantial leakage during phase transitions. Nevertheless, the as-fabricated phase-change fabrics still suffer from a complicated manufacturing procedure and poor shape stability during the phase-change process.…”
Section: Introductionmentioning
confidence: 99%
“…A concentrating technique using an optical system was developed recently to focus on thermal energy into the localized region, which is beneficial to maximize the captured solar energy. 25–27 However, since the heat conduction in traditional TIMs is either randomly distributed or unidirectional, 28,29 realizing the rapid and multidirectional thermal conductive property within TIMs for efficient thermal charging and TE discharging remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently, Philip and his group found that the thermal conductivity and light absorption of PCMs can be significantly improved by adding cheap carbon blacks . At a high filler content or employing some judicious structural engineering methods, the thermal charging rate of the PCM could be further ameliorated, reflected by its significantly improved thermal conductivity. However, merely high thermal conductivity cannot guarantee the adequate storage of thermal energy in the PCM. The thermal management efficiency of PCMs needs to be designed to be conformable to their practical applications. For example, when strong sunlight is focused onto a localized region at the top surface of the PCM, heat conduction within the PCM requires exquisite manipulation according to the heat-conduction characteristic within the STEG.…”
Section: Introductionmentioning
confidence: 99%